Effectiveness and Safety of Toripalimab Combination Therapies for Patients With Chemo-Resistant Choriocarcinoma - Liu, Xiaomei; Li, Xiuqin; Qu, Hui; Zhang, Shiyue; Zhang, Ruizhe; Du, Zhenhua (Frontiers in Oncology, 2022)
Toripalimab as a novel PD-1 inhibitor has presented its promising efficacy in patients who developed chemo-refractory carcinomas. Whereas, no study has ever investigated the effectiveness of toripalimab in chemo-resistant choriocarcinoma. Here we reported the effectiveness and safety data of 4 patients with chemo-resistant choriocarcinoma who underwent PD-1 antibody therapy by toripalimab and individualized chemotherapies. From January 2019 to August 2020, 4 patients with choriocarcinoma were admitted in Shengjing Hospital of China Medical University. Patients’ age ranged from 29 to 52 years with a median of 36 years. All patients achieved CR after the combined therapy of toripalimab with individualized chemotherapies according to the decreased serum β-hcg level. Two of four patients were observed with treatment-related adverse events (AEs), including one grade I skin rash and one grade I pruritus. Our cases showed that toripalimab combined with chemotherapy would present a tolerable safety profile and promising effectiveness in patients with chemo-resistant choriocarcinoma, indicating its potential as salvage therapy for this subset of patients.